Personalized News Communication and Media Trust in the Modern Era - Johnson, Kirsten. author. aut Link
XVI, 209 p. 31 illus., 30 illus. in color.
Keywords: This book examines the role of media credibility and trust in news personalization and consumer engagement in the US. While much has been written about the use of algorithms in audience targeting, we define news personalization in a different way: as attempts by news personnel to build credibility and trust with consumers through a focus on relatable news. The book examines tactics such as the use of transparency cues in stories, responsiveness to audience comments, and disclosing personal information to consumers. It also addresses the challenges of news personalization, including how messaging from vested interests may also be seen by audiences as personalized news. In an age when individuals are increasingly determining their own ecology of news sources, this book offers a unique perspective on an emerging area of news customization and personalization.